Production, purification and characterization of chitinase from Micromonospora sp. AR17 - Yohanes Harvinda; Ustadi Ustadi; Masagus Muhammad Prima Putra (Universitas Gadjah Mada, 2023)
N‐acetylglucosamine (NAG) is the monomer product of chitin, which has been widely used as a bioactive com‐ pound in applications such as anti‐tumor, anti‐microbial, and antioxidant activities. In production, biological processes using enzymes are preferable to chemicals due to environmental issues. This study aims to determine the activity, purity level, and molecular weight of purified chitinase from Micromonospora sp. AR17 determines the concentration of NAG produced by purified chitinase that has been characterized. Chitinase was produced by fermentation in colloidal chitin broth at 40 °C, pH 7, for 7 days, while chitinase activity was checked every 24 h. The optimal fermentation time was used to produce chitinase for a further purification step. Enzyme purification was carried out by ultrafiltration, ammonium sulfate precipitation, ion exchange chromatography (Q Sepharose Fast Flow), and gel filtration (Sephacryl S‐300). The purified enzyme was then char‐ acterized for optimum time, pH, and temperature to produce NAG. The results suggested that the fourth day was the optimal time for chitinase production, with chitinase activity of 0.0040 U/mL and a NAG concentration of 7.62 µg/mL. The purifica‐ tion step successfully increased the purity by 6.82 times with chitinase‐specific activity at 1.4648 U/mg. Production of NAG with purified chitinase produced a NAG concentration of 32.472 µg/mL with an incubation time of 30 min at 40 °C and pH 7.